Reconfigurations of Identity in Mixed Realities: the Virtual, Corporeality and the New Post-Human - Gomes, Clara (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
COVID 19 confinements changed our relationship with the computer: we use it more but not necessarilly better. In these times education, work, entertainment and art resort to social media, video streamming and online platforms. We believe that the current reflection on this Human Computer Interaction can gain from the experiments of cyberformance – the performance art the crosses physical and virtual environments – both at a theoritical level, through concepts like virtual reality or corporeality, and at an empirical level, previewing the creation of intermedial interfaces that develop our post-human condition in a more embodied, integrated and freer way.